Relationship of Anxiety Level And Knowledge of Pregnant Women in Trimester III Facing Delivery Preparation - Fadmiyanor, Isye; Rahman, Yessy Trisna; Helina, Siska; Susanti, Ari (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2022)
Physical and psychological changes in pregnancy can be a stressor that causes anxiety. The causes of anxiety in pregnant women include lack of knowledge. Not infrequently pregnant women have thoughts that interfere with their mindset so that pregnant women are less prepared for childbirth. This study aims to determine the relationship between anxiety and knowledge of pregnant women in the third trimester with preparation for delivery, is a quantitative study with a cross sectional design conducted at the Teluk Belitung Public Health Center. The research population was all third trimester pregnant women with a sample of 36 respondents. The sampling technique was accidental sampling, using the chi square statistical test. The results showed that there was a relationship between the level of anxiety of pregnant women in the third trimester with preparation for delivery (pValue 0.007) and there was no relationship between knowledge of pregnant women in the third trimester and preparation for delivery (pValue 0.061). For health workers, especially village midwives, to always provide positive support, information and motivation to pregnant women regarding pregnancy, childbirth, postpartum and newborns